TEORI BELAJAR DAN KONTRIBUSINYA TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KAJIAN LITERATUR - Etika Pujianti; Senja Dwi Lestari; Anwar Dwi Maulana; Rizki Mubarok; Ari Kusuma Wati; Ratna Widiya Puspita Sari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the application of learning theories in Islamic Religious Education (PAI) learning and analyze their contributions to improving the quality of learning. The research employed a qualitative approach using a library research method. Data sources were obtained from various scientific journal articles, books, and relevant literature discussing behavioristic, cognitivistic, constructivistic, and humanistic theories in PAI learning. Data collection techniques were carried out through documentation, while data analysis used content analysis techniques. The results of the study indicate that behavioristic theory plays a role in shaping students’ religious habits and discipline through habituation and behavioral reinforcement. Cognitivistic theory helps improve students’ understanding and thinking skills regarding PAI materials. Constructivistic theory encourages students to actively construct knowledge through learning experiences and social interaction, while humanistic theory contributes to the development of students’ emotional, spiritual, and character aspects comprehensively. In addition, the integration of various learning theories is considered capable of creating PAI learning that is more effective, active, meaningful, and relevant to the needs of students in the modern era. Thus, the integrated application of learning theories can help improve the quality of PAI learning and shape students who possess religious understanding, religious attitudes, and noble character. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan penerapan teori belajar dalam pembelajaran Pendidikan Agama Islam (PAI) serta menganalisis kontribusinya terhadap peningkatan kualitas pembelajaran. Penelitian menggunakan pendekatan kualitatif dengan jenis studi pustaka (library research). Sumber data diperoleh dari berbagai artikel jurnal ilmiah, buku, dan literatur relevan yang membahas teori behavioristik, kognitivistik, konstruktivistik, dan humanistik dalam pembelajaran PAI. Teknik pengumpulan data dilakukan melalui dokumentasi, sedangkan analisis data menggunakan teknik analisis isi (content analysis). Hasil kajian menunjukkan bahwa teori behavioristik berperan dalam membentuk kebiasaan dan disiplin religius peserta didik melalui pembiasaan dan penguatan perilaku. Teori kognitivistik membantu meningkatkan pemahaman dan kemampuan berpikir peserta didik terhadap materi PAI. Teori konstruktivistik mendorong peserta didik untuk aktif membangun pengetahuan melalui pengalaman belajar dan interaksi sosial, sedangkan teori humanistik berkontribusi dalam pengembangan aspek emosional, spiritual, dan karakter peserta didik secara menyeluruh. Selain itu, integrasi berbagai teori belajar dinilai mampu menciptakan pembelajaran PAI yang lebih efektif, aktif, bermakna, dan relevan dengan kebutuhan peserta didik di era modern. Dengan demikian, penerapan teori belajar secara terpadu dapat membantu meningkatkan kualitas pembelajaran PAI serta membentuk peserta didik yang memiliki pemahaman keagamaan, sikap religius, dan akhlak mulia.